Epithelial HIF2 alpha expression induces intestinal barrier dysfunction and exacerbation of arthritis - Wen, Jinming; Lyu, Pang; Stolzer, Iris; Xu, Jin; Gießl, Andreas; Lin, Zhen; Andreev, Darja; Kachler, Katerina; Song, Rui; Meng, Xianyi; Cao, Shan; Guggino, Giuliana; et al. (Annals of the Rheumatic Diseases, 2022)
To investigate how the mucosal barrier in the intestine influences the development of arthritis, considering that metabolic changes in the intestinal epithelium influence its barrier function. Intestinal HIF2α expression peaked at onset of experimental arthritis and RA. Conditionally, deletion of HIF2α in gut epithelial cells inhibited arthritis and was associated with improved intestinal barrier function and less intestinal and lymphatic Th1 and Th17 activation. Mechanistically, HIF2α induced the transcription of the pore-forming claudin (CLDN)-15, which inhibits intestinal barrier integrity. Furthermore, treatment with HIF2α inhibitor decreased claudin-15 expression in epithelial cells and inhibited arthritis and littermate control mice. The gut intestinal HIF2α target genes were delineated by chromatin immunoprecipitation and luciferase experiments. Furthermore, pharmacological HIF2α inhibitor PT2977 was used for inhibition of arthritis. These findings show that the HIF2α-CLDN15 axis is critical for the breakdown of intestinal barrier function at onset of arthritis, highlighting the functional link between intestinal homeostasis and arthritis.
CRIS-Team WoS Importer:2022-07-01
Keywords: Arthritis; Arthritis; Experimental; Inflammation.

Fra-2/AP-1 regulates melanoma cell metastasis by downregulating Fam212b - Chen, Guang Liang; Li, Rui; Chen, Xiao Xiang; Wang, Juan; Cao, Shan; Song, Rui; Zhao, Ming Chun; Li, Li Ming; Hannemann, Nicole; Schett, Georg; Qian, Cheng; Bozec, Aline (Cell Death and Differentiation, 2020)
Metastatic melanoma remains a challenging disease. Understanding the molecular mechanisms how melanoma becomes metastatic is therefore of interest. Herein we show that downregulation of the AP-1 transcription factor member Fra-2 in melanoma cells is associated with an aggressive melanoma phenotype in vitro and in vivo. In vitro, Fra-2 knockdown in melanoma cells promoted cell migration and invasion associated with increased Snail-1, Twist-1/2, and matrix metalloproteinase-2 (MMP-2) expression. In vivo, Fra-2 knockdown in a melanoma cell line led to increased metastasis into the lungs and liver. The increased metastatic potential of Fra-2 knockdown melanoma cells was likely due to an accelerated cell cycle transition and increased tissue angiogenesis. Using Fra-2 knockdown cell lines microarray analysis, we identified the protein Fam212b (family with sequence similarity 212 member B) as a downstream target of Fra-2. By additional knockdown of Fam212b in Fra-2 mutant cells, we mitigated the cell migration, invasion, and cell cycle transition phenotype induced by Fra-2 knockdown. Furthermore, Fam212b overexpression enhanced β-catenin pathway. Finally, Fam212b expression is correlated with increased melanoma metastasis and poor clinical outcomes in human patients. In summary, these findings reveal the Fra-2-Fam212b axis as a new pathway of melanoma metastasis, which can be in the future used as potential marker of the metastatic properties of melanoma.
CRIS-Team Scopus Importer:2020-11-20

High-fat-diet-associated intestinal microbiota exacerbates psoriasis-like inflammation by enhancing systemic γδ T cell IL-17 production - Sonomoto, Koshiro; Song, Rui; Eriksson, Daniel; Hahn, Anne Maria; Meng, Xianyi; Lyu, Pang; Cao, Shan; Liu, Ning; Taudte, Verena; Wirtz, Stefan; Tanaka, Yoshiya; Winkler, Thomas; et al. (Cell Reports, 2023)
Although it is known that psoriasis is strongly associated with obesity, the mechanistic connection between diet and skin lesions is not well established. Herein, we showed that only dietary fat, not carbohydrates or proteins, exacerbates psoriatic disease. Enhanced psoriatic skin inflammation was associated with changes in the intestinal mucus layer and microbiota composition by high-fat diet (HFD). Change of intestinal microbiota by vancomycin treatment effectively blocked activation of psoriatic skin inflammation by HFD, inhibited the systemic interleukin-17 (IL-17) response, and led to increased mucophilic bacterial species such as Akkermansia muciniphila. By using IL-17 reporter mice, we could show that HFD facilitates IL-17-mediated γδ T cell response in the spleen. Notably, oral gavage with live or heat-killed A. muciniphila effectively inhibited HFD-induced enhancement of psoriatic disease. In conclusion, HFD exacerbates psoriatic skin inflammation through changing the mucus barrier and the intestine microbial composition, which leads to an enhanced systemic IL-17 response.
CRIS-Team Scopus Importer:2023-07-28
Keywords: CP: Immunology; CP: Microbiology; high-fat diet; psoriasis; γδT cell

INTESTINAL HIF1 alpha EXPRESSION PROTECTS AGAINST EPITHELIAL CELL DEATH IN ARTHRITIS - Lyu, Pang; Wen, Jinming; Stolzer, Iris; Gießl, Andreas; Song, Rui; Meng, Xiangjun; Cao, Shan; Günther, Claudia; Schett, Georg; Bozec, Aline (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis

L-ARGININE REPROGRAMS OSTEOCLAST PURINE METABOLISM AMELIORATING BONE LOSS IN RHEUMATOID ARTHRITIS - Cao, Shan; Song, Rui; Meng, Xianyi; Kachler, Katerina; Fuchs, Maximilian; Meng, X.; Li, Y.; Taudte, Verena; Kunz, Meik; Schlötzer-Schrehardt, Ursula; Schleicher, Ulrike; Chen, X.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Metabolic rewiring controlled by HIF-1α tunes IgA-producing B-cell differentiation and intestinal inflammation - Meng, Xianyi; Asadi Asadabad, Sahar; Cao, Shan; Song, Rui; Lin, Zhen; Safhi, Mohammed; Qin, Yi; Tcheumi Tactoum, Estelle Manuella; Taudte, Verena; Ekici, Arif Bülent; Mielenz, Dirk; Wirtz, Stefan; et al. (Cellular & Molecular Immunology, 2024)
Germinal centers where B cells undergo clonal expansion and antibody affinity maturation are hypoxic microenvironments. However, the function of hypoxia-inducible factor (HIF)-1α in immunoglobulin production remains incompletely characterized. Here, we demonstrated that B cells lacking HIF-1α exhibited significantly lower glycolytic metabolism and impaired IgA production. Loss of HIF-1α in B cells affects IgA-producing B-cell differentiation and exacerbates dextran sodium sulfate (DSS)-induced colitis. Conversely, promoting HIF-1α stabilization via a PHD inhibitor roxadustat enhances IgA class switching and alleviates intestinal inflammation. Mechanistically, HIF-1α facilitates IgA class switching through acetyl-coenzyme A (acetyl-CoA) accumulation, which is essential for histone H3K27 acetylation at the Sα region. Consequently, supplementation with acetyl-CoA improved defective IgA production in Hif1a-deficient B cells and limited experimental colitis. Collectively, these findings highlight the critical importance of HIF-1α in IgA class switching and the potential for targeting the HIF-1α-dependent metabolic‒epigenetic axis to treat inflammatory bowel diseases and other inflammatory disorders.
CRIS-Team Scopus Importer:2024-11-22
Keywords: B cells; HIF-1α; Hypoxia; IgA; Intestinal inflammation

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid